Composition and medicinal applications of Citrus essential oils: Current insights and future perspectives - Farah Aprisza Sheelmarevaa; Pramesthi Reitza Navisya Vasall; Nandang Permadi; Asep Harja; Sarifah Nurjanah; Jamaludin Al-Anshori; Euis Julaeha (Phytomedicine Plus)
Citrus essential oils (CEOs) are volatile aromatic compounds derived from various plant structures, such as peels, leaves, flowers, and seeds, with unique chemical compositions influenced by species, climate, and extraction methods. CEOs, rich in terpenes and terpenoids, exhibit diverse biological activities, including antimicrobial, antioxidant, and anti-inflammatory properties. These oils have shown significant potential in combating infectious diseases and preserving food, alongside applications in the pharmaceutical, cosmetic, and perfume industries. This review summarizes current knowledge on CEOs' using PRISMA methodology focusing in chemical composition and biological activities, emphasizing their medicinal applications, such as anticancer and antimicrobial activities, and the mechanisms underlying their effects. In addition, it evaluates the benefits and challenges of their use in modern medical settings, highlighting their potential as natural agents for enhancing public health.